Community policing in Sierra Leone: Local policing partnership boards - Peter Albrecht; Olushegu Garber; Ade Gibson; Sophy Thomas (Danish Institute for International Studies (DIIS), 2014)
What can we learn from how community policing has evolved in Sierra Leone? This report answers the question by presenting an in-depth analysis of Local Policing Partnership Boards (LPPBs), the main institutional response to community needs by the Sierra Leone Police (SLP). A general understanding of how LPPBs operate is available, but there is a dearth of concrete and systematic analysis of how LPPBs in Sierra Leone's 33 police divisions operate. The report is based on data collected in 17 of Sierra Leone's police divisions and makes the following broad observations: * One of the key strengths of the LPPBs is that they are built around already existing actors of authority at the local level such as traditional leaders, quasi-vigilante groups and secret societies. This is also one of the reasons why it is difficult to ascertain if these actors would have played a central role in local order-making, regardless of whether LPPBs had been established or not. It is clear, however, that LPPBs have supported the (re)formalization of relations between the police (state) and local communities (population). [...]
Keywords: 300